THE USE OF SHORT STORY AS MEDIA IN TEACHING NARRATIVE WRITING SKILL AT THE THIRD LEVEL OF INSTITUT PRIMA BHAKTI ( IPB ) PAMEKASAN - Nurul Jamila (Universitas Madura, 2021)
Writing is one of English skill. Writing is the most difficult skill to be mastered. The using of short story as media make the students easier to be the best writer. The researcher research the English teacher at IPB in using short story as media in teaching narrative writing skill. The purpose of this research are to know how the english teacher use short story as the media in teaching writing at third level of Institut Prima Bhakti (IPB) Pamekasan, second to know the students obtacle in using story as the media in teaching writing at third level of Institut Prima Bhakti (IPB) Pamekasan, and the third is to know the students responses the use of short story as media in teaching writing at third level of Institut Prima Bhakti (IPB) Pamekasan. The method used in this research was qualitative research. It was held on 20 June until 25 July 2016. In this class there were 12 students, 10 boys and 2 girls. The researcher used get the data are observation, interview, and documentation. The use of short story as media at IPB pamekasan is based by Ghasemy procedure there four steps in using short story in teaching narrative the first is pre-activities where students required to identify the new vocabulary a ttext of short story in group work, then discussed it in class. Second activities is comprehension work the teacher can help students prepare questions which can ultimately lead to the overall understanding of the text and explain narrative text. After that is Textual analysis and group work here the teacher started to ask the students to rewrite the story of the short story that their alredy disscussed. And the last is post-assignment or further task, the teacher asked the students to compose narrative text